(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Providing feedback to the student responses in the oral questioning process is an essential element in helping the students to understand the concept of mathematics. This study was conducted to describe the types of feedback given by primary school mathematics teachers regarding the student response in the oral questioning process when teaching mathematics. This qualitative study employed a multiple case study research design. The data was obtained through observation methods, interviews, document analysis, and field notes. The data collected was analyzed using the constant comparative analysis method to obtain the themes and sub-themes within the primary data. The selection of the study participants used the purposive sampling method, resulting in a total of six primary school mathematics teachers consisting of three new teachers and three experienced teachers. This study found that both the novice and experienced teachers provided a variety of feedback for the students’ responses to the oral questioning activities during the mathematics teaching process, such as repeated trial feedback, explanatory feedback and easier questions feedback. This research provides a deeper understanding of how the different types of feedback given by the teachers as part of the oral questioning activities helps the students to stimulate their thinking.